A Single‐Center, Randomized, Double‐Blind, Active, and Placebo‐Controlled Study of KAI‐1678, a Novel PKC‐Epsilon Inhibitor, in the Treatment of Acute Postoperative Orthopedic Pain. Issue 6 (8th April 2013) - Moodie, John E.; Bisley, Eileen J.; Huang, Saling; Pickthorn, Karen; Bell, Gregory
Abstract Objective KAI‐1678, a novel inhibitor of the interaction of the epsilon isoform of protein kinase C (εPKC) with its intracellular receptor, has demonstrated activity in countering hyperalgesia in several models of pain. In this controlled randomized trial, KAI‐1678 was tested for analgesic activity in an orthopedic acute postoperative pain setting. Design Following hip or knee replacement surgery, subjects were treated with KAI‐1678, ketorolac, or saline. Subjects recorded their pain intensity on a visual analog scale and rated their quality of analgesia. The pain intensity differences between baseline and the evaluations were summed over the first 4 hours. Results The analysis revealed that, while ketorolac displayed good analgesic activity, KAI‐1678 was not significantly different than placebo. Analgesia quality ratings similarly did not show a difference between KAI‐1678 and placebo in this pain model. A small excess of infusion site erythema was seen with KAI‐1678, but otherwise the drug was safe and well tolerated. Conclusions We investigated the safety and efficacy of a novel inhibitor of εPKC and provide clinical evidence that inhibition of εPKC with KAI‐1678 is not effective in the treatment of acute postoperative orthopedic pain.